INTEGRATING THE CONCEPT OE SUSTAINABLE DEVELOPMENT INTO NATIONAL POLICIES: THE ROLE OF INDONESIAN GOVERNMENT IN TOURISM DEVELOPMENT - Micke Anggraini, Luh (JURNAL KEPARIWISATAAN, 2007)
Tourism in Indonesia has rapidly developed and has supported economic developmentof the country over three decades. Along with the issues of globalsustainability, most governments in the world, including Indonesia, have committedto develop tourism in a sustainable manner. The national tourism policythus becomes an important tool to control the development, where the naturaland cultural resources are intensively utilized to support tourism. As afocal part in policy making, the national government has a significant role toensure the attainment of sustainable tourism. However, the integration of theconcept of sustainable development in the national tourism policy has beenmoderated when the economy of Indonesia particularly in the tourism industryis currently facing a depression and has not get back to the level as achievedin the past decade.